Analisis Pola Persebaran Perumahan Average Nearest Neighbor (ANN) Menggunakan Sistem Informasi Geografis (SIG) di Kecamatan Tawang Kota Tasikmalaya - Danu Juliansyah; Dila Laila Ramadani; Ismazhenar Ismazhenar; Siti Fadjarajani Fadjarajani; Cahya Darmawan (Universitas Negeri Gorontalo, 2025)
This study aims to evaluate the housing distribution patterns in Tawang District, Tasikmalaya City, which is a central urban area experiencing rapid residential infrastructure development. Limited land availability, increasing population, and urbanization pressures have led to increasingly complex pattern changes, necessitating mapping of housing distribution patterns to understand city growth trends. The technique applied is a quantitative approach using Average Nearest Neighbor (ANN) analysis on housing location data derived from satellite image interpretation. The analysis results reveal that the housing distribution exhibits a dispersed pattern, as evidenced by a nearest neighbor ratio of 1.41 and a Z-score of 2.82, indicating statistical significance. This dispersed pattern is influenced by factors such as accessibility, changes in land use, and spatial planning policies designating Tawang District as a strategic area with mixed-use functions. In addition, there are indications that space usage is not always appropriate, considering that some housing appears outside the official residential zones. These findings emphasize the importance of better monitoring of space usage so that housing development can align with existing spatial plans. Overall, this study provides insights into the spatial dynamics of housing growth, which play a crucial role in urban planning.